A beneficial relationship: associated trees facilitate termite colonies (Macrotermes michaelseni) in Namibia. Issue 7 (26th July 2021) - Wildermuth, B.; Oldeland, J.; Juergens, N.
Abstract: In many tropical ecosystems, termites are important ecosystem engineers. Mound‐building termite species often contribute to topographical landscape heterogeneity, and the associated accumulation of soil moisture and nutrients affects the spatial distribution of plant communities. Plants that grow next to the termite mound are known to benefit from the provided nutrients and water storage. The other way around, protection against erosion and cooling effects on the microclimate of the mounds imposed by associated trees have been described. However, little is known regarding the influence of tree parameters and the long‐term effects on colony development. In an interval of 12 yr, we studied all Macrotermes michaelseni mounds occurring within one square kilometer of Namibian thornbush savanna in terms of morphology, life history, and associated plants, with a focus on the role of associated trees which grow directly adjacent to the termite mounds. Here, we present the results of a combined analysis of the character states recorded at the termite mound and the associated trees. More than 50% of all 345 recorded termite mounds were associated with a tree. Mounds with associated trees showed increased activity, growth, and height. Mound growth within the study period was correlated positively with the canopy coverage by the associated tree, while total mound heights were correlated non‐linear with medium canopy coverage of about 40%. Mounds with a tree covering the sun's average zenith (north) were taller, grew most within 12 yr, and were more likely to be active than those with no northern canopy coverage. Mounds associated with the evergreen Boscia albitrunca attained highest average height (195.06 ± 11.76 cm). We conclude that vital parameters like growth, size, and activity of the termite colonies are facilitated by shading associated trees. These benefits were shown to take significant effect within the span of 12 yr. This indicates a proper long‐term mutualism, not a loose alliance and not an obligative eu‐symbiosis. Therefore, we propose to use the term "partner tree" for trees associated with M. michaelseni mounds.